The Link between Serum Omentin Level and Insulin Resistance Biomarkers, Lipid Profile, and Atherogenic Indices in Iraqi Obese Patients. - Tahrir Etihad Kadium; Abdulhadi Alrubaie; Salim Abd Mohammed Ghanim (Baghdad Science Journal, 2023)
Omentin (or intelectin) is a main visceral fat secretory adipokine.  There is a growing interest to link omentin, obesity and co-morbidity factors. The aim of the present study is to evaluate serum omentin and its association to insulin resistance biomarkers, lipid profile and atherogenic indies. This cross – sectional study was conducted in Obesity Research and Therapy Unit-Alkindy College of Medicine by recruiting (115) individuals; 49 males /66 females. Subjects between (20 to 60) years of age were selected and classified into two groups according to their Body mass index (BMI). Group1 involved healthy lean volunteers (25 male/ 36 female; BMI 18.5 - 24.9). Group2 involved obese subjects; (24 male / 36 female with BMI ≥ 30). The study shows that obese group has higher omentin levels compared to the healthy lean group (15.49 ± 4.20 vs. 10.15 ± 5.04 pg/ml, P <0.001). In addition; obese group exhibited significantly higher levels waist circumference (WC), waist to hip ratio (WHR), glucose, insulin, homeostatic module of insulin resistance (HOMA2-IR) and lipid profile and lower levels of HDL-Chol (P <0.05). Omentin levels were significantly and positively correlated with WC, WHR, BMI, glucose, hemoglobin A1c, HOMA2-IR, triglyceride, total cholesterol, low density lipoproteins - cholesterol, triglyceride to glucose index (TyG index) and atherogenic index of plasma (AIP); (P< 0.05). Multiple regression analysis established that omentin levels was found to be associated with glucose, total Chol, TyG index and AIP in total population. These findings indicate that serum omentin levels are higher in obese individuals compared to lean subjects. Furthermore, omentin was linked to insulin resistance biomarkers and other risk factors indices such as AIP and TyG. Omentin can be used as a metabolic marker in obese.